K-9 hideout - Heiter, Elizabeth (Heiter, Elizabeth. K-9 Alaska novel., 2021)
Alaskan police handler Tate Emory and his K-9 Sitka must protect Sabrina Jones from her stalker while protecting themselves from the corrupt Boston cops Tate brought to justice.